Pemanfaatan Free Apps dan Open-source Software sebagai Alternatif Pembelajaran Online SD Negeri 1 Terong Tawah - Arik Aranta; I Gede Pasek Suta Wijaya; Ario Yudo Husodo; Fitri Bimantoro; Gibran Satya Nugraha; Muhammad Khaidar Rahman (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
SD Negeri 1 Terong Tawah is an elementary school with an A accreditation and has implemented the 2013 curriculum (K-13). Along with implementing learning from home during the Covid-19 Pandemic, SDN 1 Terong Tawah has not implemented e-learning due to limited resources. Not all students have adequate devices to access the internet. This causes the learning process to be not optimal. In addition, the teachers of SD Negeri 1 Terong Tawah and academic staff are not familiar with online learning. In this case, the teachers are required to be able to manage creative content so that the online-based learning media that is applied can be easily understood and enjoyable to use, and no less important. The application is used, which must answer the problem, where every student does not all have a smartphone device. Through training activities on the use of e-learning that is open source, it is expected to be a solution that can answer the questions faced, where the applications developed are free media and can be opened on various internet-connected devices such as laptops/computers/smartphones, are web-based so that no installation process required.